Organizational Commitment, Workload, and Organizational Justice as Predictors of Turnover Intention at PT Hi-Lex Cirebon - Ferdy Arianto; Kartono (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study analyzes the effect of organizational commitment, workload, and organizational justice on turnover intention among employees of PT Hi-Lex Cirebon. The study used a quantitative explanatory design with questionnaire data from 100 employees selected through purposive sampling. Data were analyzed using SPSS through validity, reliability, classical assumption, multiple regression, t-test, F-test, and coefficient of determination. The results show that the three variables have significant partial and simultaneous effects on turnover intention, with workload as the strongest predictor. The policy synthesis recommends workload balancing, stronger employee commitment, and more transparent organizational justice practices to support employee retention.